It’s a ‘plandemic’, not a pandemic: unraveling the discourse of a global conspiracy to destroy Islamic faith through COVID-19 health protocols - Irawan, Andi Muhammad; Alamsyah, Devy Kurnia; Iskandar, Iskandar; Nasmilah, Nasmilah; Hadisaputra (Indonesian Journal of Islam and Muslim Societies, 2025)
This paper aims to investigate the discursive arguments surrounding COVID-19 health protocols, particularly those related to prayer restrictions for Indonesian Muslims during the pandemic. The study highlights the importance of examining the development of contemporary Indonesian Islam and how particular Muslims address social and health issues that touch on sensitive religious matters through various religious interpretations. It explores how different religious sermons are discursively constructed by Muslim scholars to oppose the implementation of protocols restricting prayer, such as prayer distancing, mosque closures, and praying from home. The study employs topoi analysis as one approach in Critical Discourse Analysis (CDA) to examine how arguments are utilized in texts and talks to justify specific claims. The study finds that several topoi are used to justify the claim that COVID-19 is a ‘plandemic’ or a global conspiracy orchestrated by Judaism to destroy the Islamic faith. These arguments are specifically framed using the topos of enmity, faith, threat, or danger, definition or name-interpretation, and the topos of law.